Toxoplasma and Africa: One Parasite, Two Opposite Population Structures. Issue 2 (February 2018) - Galal, Lokman; Ajzenberg, Daniel; Hamidović, Azra; Durieux, Marie-Fleur; Dardé, Marie-Laure; Mercier, Aurélien
Abstract : Exploring the genetic diversity of Toxoplasma gondii is essential for an understanding of its worldwide distribution and the determinants of its evolution. Africa remains one of the least studied areas of the world regarding T. gondii genetic diversity. This review has compiled published data on T. gondii strains from Africa to generate a comprehensive map of their continent-wide geographical distribution. The emerging picture about T. gondii strain distribution in Africa suggests a geographical separation of the parasite populations across the continent. We discuss the potential role of a number of factors in shaping this structure. We finally suggest the next steps towards a better understanding of Toxoplasma epidemiology in Africa in light of the strains circulating on this continent. Trends: There is a demarcation of T. gondii populations between the tropical zone and the arid zones of Northern and Eastern Africa. Tropical Africa shares common haplogroups with South America, whereas Northern and Eastern Africa are dominated by archetypal lineages types II and III, which are also the main lineages in Europe and North America. The determinants of this structure are poorly understood. In Africa, lack of awareness and diagnostic tools makes it especially difficult to understand the real burden of human toxoplasmosis and the contribution of the parasite's genotype to the disease severity.